UPGRADING PHRATHATPHANOM TO BE A PARTICIPATORY CULTURAL WORLD HERITAGE OF PEOPLE ON BOTH SIDES OF THE MEKONG - Thokaew, Marvin; Saibua, Papangkorn; Singngoi, Likhasit (Journal of Buddhist Education and Research (JBER), 2024)
The objectives of this research were as follows: 1) to study the role of Phra That Phanom from the Urangkhathat legend; 2) to study Phra That Phanom with the participation of people on both sides of the Mekong River; and 3) to provide guidelines for uplifting Phra That Phanom to a cultural world heritage site. The main qualitative informants were: 1. 20 knowledgeable and local philosophers, representatives of the government, private sector, and related agencies in Nakhon Phanom Province; and 2. 15 local knowledgeable people and philosophers living in Ban Si Khot Bura, Mueang Khammouane, Laos PDR. While the quantitative informants were 100 people living in both target areas. The research tools used for the data collection were interviews and questionnaires. The research revealed that: 1) The legend of Urangkhathat mentions enshrining the chest bone of the Lord Buddha at Phra That Phanom and being the center of faith and beliefs of Buddhists around the world. It promoted the local economy. 2) Participation in uplifting the Phra That Phanom to be a world cultural heritage site consisted of five elements, as follows: 1) setting up a committee; 2) organizing a public forum; 3) organizing educational activities; 4) exchanging information; and 5) promoting knowledge by cooperating with every related sector. 3) Guidelines for uplifting Phra That Phanom to become a world cultural heritage site were as follows: (1) Prepare an order to appoint an operating committee; (2) The province should allocate a budget to support operations; (3) Prepare an operational plan for elevating Phra That Phanom to a World Cultural Heritage Site; (4) Operate according to plan, monitor, and evaluate from government and private agencies; (5) Every process should have the participation of local people from every district in Nakhon Phanom Province along with related government and private agencies.